Energy Statistics Yearbook 2021 - United Nations Department of Economic; Social Affairs (United Nations, 2024)
This publication contains detailed national accounts estimates for 178 countries and areas of the world for the reporting year 2000. The estimates for each country or area are presented in separate chapters with uniform table headings and classifications as recommended in the United Nations System of National Accounts (SNA). A summary of the SNA conceptual framework, classifications and definitions are included in this publication. National Accounts Statistics: Main Aggregates and Detailed Tables contains statistics in such areas as: gross domestic product, national income, savings, private and government consumption, and transactions of institutional sectors. It is a valuable source of information on the economic situation of countries.